Why are the developmental disturbances an issue in psychology? The question of IQ stability in children with specific learning disorders - Krstić Nadežda; Obradović Svetlana (Psihologija, 2012)
A small group of elementary school students (age 10.4 to 13.10 yrs) with specific developmental disability of scholastic skills (app. F81.0/81.3 according to ICD-10) was retested by REVISK (locally standardized approximate of WISC-III) within, in average, 3 yrs post diagnosis, for detecting possible changes in their general ability performance. REVSIK measures were adjoined by 3 and 4-factor schemes proposed by Kaufman and Bannatyne. The results have indicated significant decline of the total IQ score (average difference=-3.0, t=2.434, df=24, t<0.05), intra-subtest variability on the verbal subscale (-1.3, t=2.397, df=24, p<0.05) and Bannatyne’s factors of Acquired Knowledge (-1.5, t=4.375, df=24, p<0.01) and Spatial factor (-0.6, t=2.701, df=24, p<0.05). No homogenous subtest profiles were detected in original either repeated testing. The results and implications for the future studies are discussed against the background of contemporary theory and research in this field, as well as of empirically-based constraints in recognizing this population in a local setting.